TUBUH SOSIAL SEBAGAI MODAL SIMBOLIK DALAM SEKTOR KERJA PARIWISATA DI KABUPATEN BADUNG - Adi Pranatha, I Ketut Primantara; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 3 No 1 (2023): JISSOROT, 2023)
This research presents the extent of the role of social body for tourism industry workers in Badung Regency. The method used in this research is a qualitative approach with a descriptive-explanatory type. The theory chosen is the social body theory by Mary Douglas. The results of this research reveal that having an attractive appearance as a symbolic capital in the tourism industry is crucial in the process. Being attractive does not only refer to facial appearance but also includes neat clothing, makeup, a good hairstyle, a good speech style, a good communication, and others. Each worker has an individual body and a social body. The individual body refers to a person's physical form, while the social body refers to when the body is in a public space. The existence of the social body is forced into existence, for example, a worker who does not need to apply makeup in their daily life at home, but when they work, they must apply makeup because of the company's rules. The social body can also become a currency because it can provide benefits if workers can present their best appearance.